Anxiety-depressive manifestations and their relationship with somatic symptoms in patients with interstitial cystitis - Bozhuk, B. S.; Stepanchenko, M. S.; Assonov, D. O. (Zaporozhye Medical Journal, 2019)
Interstitial cystitis is important not only medical, but also a social problem, because it can lead to productivity loss, neurotic states occurrence, sleep deprivation and behavior change. The study and assessment of anxiety-depressive disorders in patients with interstitial cystitis will allow to learn better the features and structure of the psychic component in the symptomatology of this pathology and to develop the most appropriate treatment strategy with the involvement of a mental health specialist to work with an urologist. Aim. To assess anxiety-depressive manifestations and their relationship with somatic symptoms in patients with interstitial cystitis. Materials and methods. A total of 44 patients (38 women and 6 men) diagnosed with interstitial cystitis / bladder pain syndrome were examined. To assess the somatic manifestations and the symptoms effect on the quality of life, the Genitourinary Pain Index (GUPI) questionnaire, the O’Leary-Sant questionnaire, the Pelvic Pain and Urgency / Frequency (PUF) Patient Symptom Scale questionnaire were used. To assess the mental manifestations, the Beck Depression Scale and the Spielberger test were used. Results. 5 of the examined patients had a low state anxiety, 11 – moderate and 28 - high state anxiety. 9 of the examined patients had a low trait anxiety, 18 – moderate and 17 - high trait anxiety. There was no correlation between state and trait anxiety indicators with the results of the GUPI questionnaire, the PUF scale, the O’Leary-Sant questionnaire. 22 subjects had mild depressive symptoms, 22 subjects had no depressive symptoms. A negative correlation was found between the degree of symptomatology according to the GUPI questionnaire and the severity of depression (rs = -0.28, P < 0.1). A direct correlation was found between the negative effect on the quality of life and the degree of depression severity (rs = +0.253, P < 0.1). Conclusions. Interstitial cystitis is always accompanied by anxiety-depressive symptoms, and anxiety symptoms are more common and expressed than depressive. Severe symptomatology may be a precondition for the development of anxiety and depressive disorders in patients, but is not a direct cause of their occurrence. Trait anxiety is not a risk factor for the early onset of the disease and its course prolongation, as well as earlier or later occurrence and longer duration of interstitial cystitis is not a prerequisite for state anxiety aggravation. Severity of depression depends directly on the negative impact of somatic symptoms on the quality of life. An integrated complex approach to the diagnosis and management involving a mental health specialist can significantly improve the effectiveness of interstitial cystitis therapy.